Pro-inflammatory cytokines in cystic glioblastoma: A quantitative study with a comparison with bacterial brain abscesses. With an MRI investigation of displacement and destruction of the brain tissue surrounding a glioblastoma - Hassel, Bjørnar; Niehusmann, Pitt; Halvorsen, Bente; Dahlberg, Daniel (Frontiers in Oncology, 2022)
Glioblastomas are aggressive primary brain tumors that may both destroy and displace the surrounding brain tissue as they grow. The mechanisms underlying glioblastomas’ destructive effect remain elusive, but could include exposure of brain tissue to tumor-derived cytokines. In the present study, preoperative MRI of 20 cystic and 10 solid glioblastomas confirmed that glioblastomas cause both destruction and displacement of brain tissue. Analysis of cyst fluid from the cystic glioblastomas allowed the quantitation of leukocyte markers and cytokines, which we compared to values in 13 brain abscess pus samples. The concentration of macrophage/microglia markers sCD163 and MCP-1 was higher in glioblastoma cyst fluid than in brain abscess pus; lymphocyte marker sCD25 was similar in cyst fluid and pus, whereas neutrophil marker myeloperoxidase was higher in pus. Cytokine values varied greatly between patients, indicating a variable inflammatory status. However, median levels were high (pg/mL): TNF-α: 32, IL-6: 1064, IL-8: 23585, tissue factor: 28, the chemokine CXCL1: 639. These values were not significantly different from values in pus, pointing to a highly pro-inflammatory glioblastoma environment. In contrast, levels of IFN-γ, IL-1β, IL-2, IL-4, IL-10, IL-12, and IL-13 were higher in pus than in glioblastoma cyst fluid. The concentration of several cytokines in glioblastoma cyst fluid correlated with blood leukocyte level, but none of the cytokine levels correlated with peri-tumoral edema or degree of brain tissue displacement, as could be assessed by MRI. We conclude that glioblastomas both displace and destroy brain tissue; these processes are accompanied by a variable degree of inflammatory activity.